2024
DOI: 10.3390/land13040466
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Geospatial Distribution of Peat Layer Thickness Using Machine Learning and Aerial Laser Scanning Data

Janis Ivanovs,
Andreas Haberl,
Raitis Melniks

Abstract: Organic horizons including peat deposits are important terrestrial carbon pools, and various chemical, biological, and water exchange processes take place within them. Accurate information on the spatial distribution of organic soils and their properties is important for decision-making and land management. In this study, we present a machine learning approach for mapping the distribution of organic soils and determining the thickness of the peat layer using more than 24,000 peat layer thickness measurements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Our results revealed that among all studied land use types of peatlands, the mean annual DOC efflux varied from 61.9 ± 4.4 kg ha −1 y −1 in grasslands to 513.1 ± 38.7 kg ha −1 y −1 active peat extraction sites. Silver birch (153.6 ± 11.2 kg ha −1 y −1 ) and Scots pine forests (328.3 ± 23.1 kg ha −1 y −1 ) are common in Latvia, where more than 10% of the total area is covered by peatlands [11,12]. The DOC efflux from Scots pine forests and all peat extraction sites coincided with values from the temperate climate zone, while efflux from silver birch forests, croplands, and grasslands were more comparable to the results from the boreal zone, which contributes to previous findings about the thermal gradient impact.…”
Section: Doc Efflux and Affecting Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results revealed that among all studied land use types of peatlands, the mean annual DOC efflux varied from 61.9 ± 4.4 kg ha −1 y −1 in grasslands to 513.1 ± 38.7 kg ha −1 y −1 active peat extraction sites. Silver birch (153.6 ± 11.2 kg ha −1 y −1 ) and Scots pine forests (328.3 ± 23.1 kg ha −1 y −1 ) are common in Latvia, where more than 10% of the total area is covered by peatlands [11,12]. The DOC efflux from Scots pine forests and all peat extraction sites coincided with values from the temperate climate zone, while efflux from silver birch forests, croplands, and grasslands were more comparable to the results from the boreal zone, which contributes to previous findings about the thermal gradient impact.…”
Section: Doc Efflux and Affecting Factorsmentioning
confidence: 99%
“…Lowering the water table by drainage is a prerequisite for peatland forestry, use for agriculture, and peat extraction in most countries [9,10]. These practices are also common in Latvia, where more than 10% of the total area is covered by peatlands [11,12]. As a result, the hydrological regime of the peatlands is altered, and mineralization of peat is promoted, resulting in increased gross C losses.…”
Section: Introductionmentioning
confidence: 99%